Impact of Eco-Tourism and Culture Tourism for Community Economy in Indonesia - Suwarno (Eastern Journal of Economics and Finance, 2019)
The purpose of this study was to describe the impact of eco and culture tourism on the economic life of the people of Gunugn Kelud, Ngancar, Kediri, East Java, Indonesia. The method used in the research is qualitative methods. Data was collected using interview and participatory observation methods. Data were analyzed using four stages of research including data collection, data classification, data filtering, and conclusion drawing. Based on the results of the analysis it was concluded that, with the existence of eco and culture tourism, the economic life of the community would increase. Eco and culture tourism are able to absorb a large number of unskilled and semi-skilled workers. Eco and Culture tourism are able to contribute to the economic enthusiasm of the community, especially people who are looking for work and economically disadvantaged communities. The community is able to send their children to school well, and is able to provide hope for a better future.